Examination of the efficacy of different fungicides against Macrophomina phaseolina and Sclerotinia sclerotiorum in laboratory conditions - Csüllög, Kitti; Biró, Györgyi; Gonsalves, Joycline David; Sanga, Stoweka Maneno; Tuly, Nowrin Mostafa; Abushawish, Abdul Kareem; Tóth, Gyula; Vartek, Cintia; Ernhardt, Nóra; Tarcali, Gábor; Csótó, András (Acta Agraria Debreceniensis, 2022)
Macrophomina phaseolina and Sclerotinia sclerotiorum are two significant fungal pathogens of sunflower. M. phaseolina causes charcoal rot and ashy stem blight in several important crop species. Sclerotinia sclerotiorum causes white mold disease which can occur as middle stalk rot, head rot and premature plant death. Due to the wide host range of the two pathogens and their survival structures, crop rotation cannot provide sufficient protection against them. In our experiment, we selected two fungicides, Mirage and Prosaro, which are widely used in practice, and we tested their efficacy against the two pathogens. The efficiency of these fungicides was tested at a concentration of 10; 20; 50; 100 and 500 ppm. The Prosaro totally inhibited the mycelial growth of both pathogens at a concentration of 50 ppm, 100 ppm and 500 ppm. The Mirage caused total mycelial growth inhibition in all treatments against both pathogens.